Sensitivity analysis of the computational model of the coal carbonisation process. (5th March 2017) - Slupik, Lukasz; Fic, Adam; Bulinski, Zbigniew; Nowak, Andrzej J.; Smolka, Jacek; Kosyrczyk, Ludwik
Highlights: The coal carbonisation process is analysed using the developed CFD model. The model is verified and tuned employing temperature measurements. Simulated temperatures are in satisfied agreement with measured ones. Sensitivity of important model parameters on the simulated temperatures is presented. Analysis shows a great importance of the specific heat and the thermal conductivity on the results. Abstract: The paper addresses the numerical analysis of the complex conjugate fluid flow and energy transport phenomena taking place in the coking chamber during the coal carbonisation process. Sensitivity analysis concerning investigation of an influence of the most important model parameters on the simulated temperatures is the main aim of the paper. The simulated temperatures are confronted with results of experimental measurements, hence quality of obtained numerical results could be assessed. Moreover, carried out analysis of the sensitivity coefficients allowed us to verify potential to retrieve uncertain model parameters using inverse methods. Particularly, an effect of the thermal conductivity of the coal blend, the coal specific heat, the evaporation model constant, the unit heat absorbed and generated due to endothermic and exothermic reactions on the temperature field is analysed. In addition, the computed sensitivity coefficients indicate that the specific heat and the thermal conductivity of the coal blend have the highest effect on the obtained temperatures. The evaporation constant has important influence only on the temperatures during evaporation and affects the evaporation time taking place at early stage of the process.